Comparative assessment of antidepressant-related behaviors of citalopram, crocin, and their combination in non-acute restraint stress and acute restraint stress mice - Maryam Parhizkari; Fatemeh Khakpai; Mohammad-Reza Zarrindast (IBRO Neuroscience Reports)
Many studies demonstrated the role of citalopram (the bromohydrate of citalopram, which inhibits 5-HT reuptake) and crocin (a carotenoid chemical compound, antioxidant, antidepressant) in the modulation of depression-related behaviors. This research aimed to assess a possible interaction between citalopram and crocin on the modulation of depression-related behaviors in non-acute restraint stress (NARS) and acute restraint stress (ARS) mice. ARS was induced using movement restraint for 4 hours. Depression-related behaviors were measured using forced swimming test (FST), tail suspension test (TST), and splash test (ST). The results indicated that induction of ARS increased immobility time in the FST and TST but decreased grooming duration in the ST, indicating depression-related behaviors. Intraperitoneal (i.p.) injection of citalopram (4 mg/kg) and crocin (40 mg/kg) separately induced antidepressant-related behaviors in the NARS and ARS mice due to the reduction of immobility time in the FST and TST but augmentation of grooming duration in the ST. Furthermore, i.p. co-treatment of citalopram (1 mg/kg) and crocin (40 mg/kg) induced stronger antidepressant-related behaviors rather than alone injection of them. Moreover, the results showed a synergistic effect between citalopram and crocin on the induction of antidepressant-related behaviors in male mice. In conclusion, our results exhibited an interaction between citalopram and crocin on the modulation of depression-related behaviors in the NARS and ARS mice.